Memory a philosophical study - Bernecker, Sven. (Oxford : Oxford University Press, 2010)
Sven Bernecker presents an analysis of the concept of propositional (or factual) memory, and examines a number of metaphysical and epistemological issues crucial to the understanding of memory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Memory (Philosophy)